Excellent overall and chronic graft‐versus‐host‐disease‐free event‐free survival in Fanconi anaemia patients undergoing matched related‐ and unrelated‐donor bone marrow transplantation using alemtuzumab–Flu–Cy: the UK experience. (14th April 2021) - Bernard, Fanette; Uppugunduri, Chakradhara Rao S; Meyer, Stefan; Cummins, Michelle; Patrick, Katharine; James, Beki; Skinner, Roderick; Tewari, Sanjay; Carpenter, Ben; Wynn, Robert; Veys, Paul; Amrolia, Persis; et al.
Summary: Haematopoietic stem cell transplantation (HSCT) remains the only curative option in Fanconi anaemia (FA). We analysed the outcome of children transplanted for FA between 1999 and 2018 in the UK. A total of 94 transplants were performed in 82 patients. Among the donors, 51·2% were matched related donors (MRD) while the remainder were alternative donors. Most patients received a fludarabine–cyclophosphamide (Flu–Cy)‐based conditioning regimen (86·6%) and in vivo T‐cell depletion with alemtuzumab (69·5%). Five‐year overall survival (OS) was 85·4% [70·4–93.2] with MRD, 95·7% [72·9–99.4] with matched unrelated donors (MUD), 44·4% [6·6–78.5] with mismatched unrelated donors (MMUD) and 44·4% [13·6–71.9] with mismatched related donors (MMRD) ( P < 0·001). Other factors significantly impacting OS were pre‐transplant bone marrow status, source of stem cells, cytomegalovirus (CMV) serostatus, preparation with Flu–Cy, use of total body irradiation (TBI) and alemtuzumab as serotherapy. In multivariate analysis, absence of myelodysplastic syndrome (MDS) or leukaemia, bone marrow as source of stem cells, cytomegalovirus (CMV) other than +/− (Recipient/Donor) and Flu–Cy were protective factors for five‐year OS. Five‐year chronic graft‐ versus ‐host‐disease (cGVHD)‐free event‐free survival was 75·4% with the same risk factors except for CMV serostatus. Five‐year non‐relapse mortality was 13·8% [7·3–22.3]. Only five patients (6·1%) developed grade II–IV acute GVHD and two patients chronic GVHD. These data confirm the excellent outcome of matched related or unrelated HSCT in children with FA.